2017
DOI: 10.3141/2666-12
|View full text |Cite
|
Sign up to set email alerts
|

Changing Influence of Factors Explaining Household Car Ownership Levels in the Netherlands

Abstract: To contribute to existing research on the influence of various factors on household car ownership in the Netherlands, this study addressed the question whether and to what extent the influence of economic, socio demographic, and spatial factors on the number of cars owned by house holds has changed over time. There seems to be an absence of studies investigating the changing influence of these factors on car ownership in recent decades, and in the Netherlands. The study used the statisti cal method of ordered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The decision to own a private vehicle and the type of vehicle depends on different HH characteristics, such as its income, size, the number of license holders, composition in full-time workers and children, education level, gender and age [1], [2]. Ha, et al (2019), using important variable ranking methods as Multi-nominal Logit model, Neural Networks and Random Forests, found that income is the most potent variable influence on motorisation among other HH characteristics [5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The decision to own a private vehicle and the type of vehicle depends on different HH characteristics, such as its income, size, the number of license holders, composition in full-time workers and children, education level, gender and age [1], [2]. Ha, et al (2019), using important variable ranking methods as Multi-nominal Logit model, Neural Networks and Random Forests, found that income is the most potent variable influence on motorisation among other HH characteristics [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Maltha, Y. (2016) found that the HH income was the most influential factor in vehicle ownership together with HH size, gender, age, education, suburbanisation, and working status in the Netherlands between 1987 and 2014 [2].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Determinants of uncertainty for the transport sector are multifaceted and include the: changing demand for travel in society, its causes and likely continuation (Marsden et al 2018;Maltha et al 2017); impacts of climate change on infrastructure resilience and investment needs (Buurman and Babovic 2016;Dawson et al 2016); speed and nature of any transition away from fossil fuel powered transport (Contestabile et al 2017;Brand et al 2019); future way in which road travel will be priced in a shift to electric vehicles (NIC 2017;Volterra Partners and Jacobs 2017); digital age maturing with a myriad of developments in information and communications technology (ICT) that in turn influence behaviours (Lyons et al 2018a); advent, deployment and impacts of increasingly intelligent, automated and connected vehicle technology (Shaheen et al 2018;Rohr et al 2015); and the traditional factors of population growth, fuel price, disposable income and land-use distribution (NIC 2016;OBR 2018).…”
Section: A Wicked Problemmentioning
confidence: 99%
“…The Dynamic Automobile market (DYNAMO) model in the Netherlands has been developed for the Dutch Transport Research Centre and the Netherlands Environmental Assessment Agency (see MuConsult, 2006;Maltha, 2016). The most important car ownership prediction model in the Netherlands, its latest version (3.0) assesses the effects of general developments and government policy on the size, composition and use of the Dutch car fleet for the period up to 2050.…”
Section: Who Is Doing What?mentioning
confidence: 99%